1991
DOI: 10.1007/bf01249114
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter markers in the cerebrospinal fluid of normal subjects effects of aging and other confounding factors

Abstract: We have investigated neurotransmitter-related markers of the cerebrospinal fluid (CSF) in a carefully screened series of normally aging subjects in standardized conditions in order to find out the influence of age and other confounding factors on CSF measures. The levels of 3-methoxy-4-hydroxyglycol (MHPG) and the activity of acetylcholinesterase (AChE) also increased with age, while homovanillic acid (HVA), 5-hydroxyindoleacetic acid (5 HIAA) and immunoreactivities of somatostatin (SLI), beta-endorphin (BLI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
2
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 61 publications
3
21
2
2
Order By: Relevance
“…The concentration of MHPG in the CSF correlated positively with age in normal subjects (Har-tikainen et al, 1991) and in AD patients (r --0.40, p = 0.04), but not in PD (r ---0.09, p = 0.61) or ALS patients (r = 0.29, p ---0.10). Seasonal alterations in the CSF levels of DBH and BLI found for normals (Hartikainen et al, 1991) were not observed for any of the disease groups. ACTH values for AD patients (p < 0.05) showed similar seasonal change as did those of controls; the levels were higher in the light than in the dark period (Hartikainen et al, 1991).…”
Section: Resultscontrasting
confidence: 46%
See 1 more Smart Citation
“…The concentration of MHPG in the CSF correlated positively with age in normal subjects (Har-tikainen et al, 1991) and in AD patients (r --0.40, p = 0.04), but not in PD (r ---0.09, p = 0.61) or ALS patients (r = 0.29, p ---0.10). Seasonal alterations in the CSF levels of DBH and BLI found for normals (Hartikainen et al, 1991) were not observed for any of the disease groups. ACTH values for AD patients (p < 0.05) showed similar seasonal change as did those of controls; the levels were higher in the light than in the dark period (Hartikainen et al, 1991).…”
Section: Resultscontrasting
confidence: 46%
“…Because age, height, weight, and season were found to interfere with the levels CSF measures in our previous work with controls (Hartikainen et al, 1991), all CSF variables but MHPG, DBH, and BLI were adjusted for age and, in addition, HVA for height and season, ACTH for season and weight and SLI for weight. The concentration of MHPG in the CSF correlated positively with age in normal subjects (Har-tikainen et al, 1991) and in AD patients (r --0.40, p = 0.04), but not in PD (r ---0.09, p = 0.61) or ALS patients (r = 0.29, p ---0.10).…”
Section: Resultsmentioning
confidence: 99%
“…Hence a bias may have been introduced with regards to diurnal and seasonal rhythms, and their effect on the levels of the markers. Effects that are difficult to standardise such as the height of subjects may effect the concentration of markers in lumbar CSF [31]. Intra-individual variations however may remain stable over a short period [32].…”
Section: Discussionmentioning
confidence: 99%
“…[y32P]2N3ATP (specific activity, [5][6][7][8][9][10][11][12][13][14] mCi/,tmol) was then prepared and purified as described for ['t-32P]8N3ATP. Protein molecular size standards were from Bio-Rad.…”
Section: Methodsmentioning
confidence: 99%
“…Amyloid, paired helical filament, and a1-antichymotrypsin immunoreactivity have been reported to be elevated in the CSF of AD patients (4)(5)(6). The CSF has also been examined for concentration changes in neuropeptides (7), biogenic amines and their metabolites (8), amino acid or amino acid derivatives (9), vitamins (10), and trace elements (11). However, none of these compounds has emerged as a reliable marker for AD.…”
mentioning
confidence: 99%